2017
DOI: 10.1002/asia.201700898
|View full text |Cite
|
Sign up to set email alerts
|

A Pyridoindole‐Based Multifunctional Bioprobe: pH‐Induced Fluorescence Switching and Specific Targeting of Lipid Droplets

Abstract: A versatile fluorescent probe, PITE, based on alkyl-substituted pyridoindole (PI) and tetraphenylethylene (TE), which exhibits facile pH-induced fluorescence switching in solution, as nanoparticles, and in the solid state, is presented. Strong fluorescence in the solid state, as well as in solution and the aggregated state, allow sensing of toxic acid vapors. Fluorescence "off-on" switching of PITE through exposure to trifluoroacetic acid and triethylamine vapor is visualized by the naked eye. A unified pictur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 77 publications
0
32
0
Order By: Relevance
“…PITE [ 28 ] arose from the combination of pyroindole (PI) and tetraphenylethylene (TE) ( Figure 3 ). PI emits strong green fluorescence in organic solvents, while its fluorescence is quenched in aqueous solution due to poor solubility and aggregation.…”
Section: Recent Developments In Lds’ Selective Fluorescent Probesmentioning
confidence: 99%
See 1 more Smart Citation
“…PITE [ 28 ] arose from the combination of pyroindole (PI) and tetraphenylethylene (TE) ( Figure 3 ). PI emits strong green fluorescence in organic solvents, while its fluorescence is quenched in aqueous solution due to poor solubility and aggregation.…”
Section: Recent Developments In Lds’ Selective Fluorescent Probesmentioning
confidence: 99%
“…The absorption spectra of PITE displays two bands at 320 and 420 nm as contributions of both moieties TE and PI respectively, while it emits at 490 nm and does not depend on excitation wavelength. Using Saccharomyces cerevisiae (as the yeast cell model) and HeLa cells (as the mammalian cell model), Sk et al showed the compatibility of PITE as a blue fluorescent LD probe [ 28 ].…”
Section: Recent Developments In Lds’ Selective Fluorescent Probesmentioning
confidence: 99%
“…Great efforts have been made to develop novel lipid droplets dyes to solve these problems. [12][13][14][15][16][17][18][19][20][21] Because the normal concentration used for lipid droplets staining falls in the range of 5-10 μM or even higher, these dyes show weak emission due to the aggregation-caused quenching (ACQ) effect. 22 Few dyes have been synthesized for lipid droplets imaging and function at nano-molar concentrations.…”
mentioning
confidence: 99%
“…We anticipated that the hydrophobic TPAn might internalize to the lipid-enriched organelles, such as lipid droplets (LDs) through the hydrophobic interactions. 67,68 The spectroscopic features of TPAn inside the living cells were probed through the fluorescence lifetime imaging (FLIM) using a time-resolved confocal microscope. A punctate dot-like pattern in the cytoplasm (ex = 405 nm, em = 435-800 nm), [69][70][71][72] found to be 9 ms (Figure 8a), which is 90 times higher than that in THF.…”
Section: Resultsmentioning
confidence: 99%